DISEMINASI PEMBUATAN PELLET IKAN BERPROBIOTIK â€œPROBIO_FMUBBâ€ KEPADA PEMBUDIDAYA IKAN - Sudirman Adibrata; Rufti Puji Astuti; Novyandra Ilham Bahtera; Rahmad Lingga (Jurnal Abdi Insani, 2023)
The abundance of trash fish in certain seasons and palm kernel cake is a wealth in Bangka Island which can be used by Pokdakan to manufacture fish feed. Technical skills are needed by Pokdakan so the transfer of knowledge from fisheries experts at the University of Bangka Belitung is important. The aim of this activity is to disseminate the manufacture of probiotic fish pellets with Probio_FmUBB, transfer knowledge of making fish pellets, and find out the proximate content. The activity was carried out in Pagarawan Village, Merawang District, Bangka Regency, as well as the pellet proximate test at the UPTD LPPMHP Bangka Belitung. The activity method is by giving lectures to convey theory to discussions and playing YouTube videos for the practice of making pellets. In preparing artificial feed, it is necessary to consider, among other things, knowing the size and type of cultivated fish, production targets of artificial feed, inventorying the availability of raw materials, preparing feed formulations and calculating them, printing feed, as well as packaging and storage. Artificial feed that has good quality must comply with the requirements needed. The nutritional composition of fish pellets must contain balanced elements of protein, carbohydrates, fats, vitamins and minerals. The procedure for making artificial fish pellets was understandable to the participants and could be practiced in their respective Pokdakan. The types and formulas of ingredients for the manufacture of fish pellets are 0.5 kg of fish meal, 0.2 kg of shrimp meal, 0.25 kg of palm kernel cake, 0.12 kg of bran, 10 bottle caps of probiotics. The proximate content is known by the value of Moisture Content 20.79%, Ash Content 20.63%, Protein 31.36%, and Total Fat 4.33%. The pellets made by Pokdakan are suitable for use as feed for cultivated fish biota, especially for tilapia and catfish.